Sorting - Bryant-Mole, Karen; Mukhida, Zul (Milwaukee : Gareth Stevens Pub., 2000)
With paintbrushes, buttons, crayons, and cups, a teddy bear helps readers learn to sort objects into sets using different criteria, such as color, shape, and texture.
Includes index.
Keywords: Set theory -- Juvenile literature; Set theory